Helicobacter Pylori Infection and the Risk of Myocardial Infarction: Role of Fibrinogen and Its Genetic Control - Zito, Francesco; Di Castelnuovo, Augusto; D’Orazio, Andria; Negrini, Riccardo; De Lucia, Domenico; Benedetta Donati, Maria; Iacoviello, Licia (Thrombosis and Haemostasis, 1999)
The contribution of Helicobacter pylori (HP) infection to the risk of myocardial infarction was evaluated. The role of fibrinogen and its genetic control as a possibile mechanism by which HP may influence myocardial infarction risk was explored in this context. A case-control study was performed in 101 patients with myocardial infarction and in 101 controls.HP infection was associated with an increased risk of myocardial infarction independently for confounding variables (OR 4.1, CI95: 1.8-9.4). HP infection was significantly associated with higher levels of fibrinogen, both in cases and in controls. Furthermore, there was an additive effect of HP infection and B2 allele of BclI fibrinogen poly-morphism in increasing fibrinogen levels. HP infection showed a stronger effect on the risk of myocardial infarction in B2 allele carriers (OR 7.6, CI95: 1.8-31.6) as compared to subjects carrying the B1B1 genotype (OR 3.3, CI95: 1.2-9.2).We showed that a previous HP infection is a risk factor for myocardial infarction. An increase in fibrinogen levels is a possible mechanism by which HP may act. Concomitant conditions, like a genetic predisposition in increasing fibrinogen levels, seem to further increase the effect of HP on myocardial infarction risk.